Effectiveness of Interventions Based on Social Marketing Theory in Promoting Healthy Eating Habits: A Systematic Review - Vahid Ranaei; Sakineh Dadipoor; Hossain Davoodi Sayed; Teamur Aghamolaei; Zahra Pilevar (Journal of Education and Community Health)
Aims: Social marketing is one of the approaches that is effective in promoting healthy eating behaviors by affecting different levels of target audience behaviors. The purpose of the present study was to determine the effectiveness of interventions based on social marketing theory in promoting healthy eating behaviors. Information & Methods: In order to identify interventions, Persian and English databases including Google Scholar, Scopus, Science direct, Web of science, PubMed, SID and, Iran medex were studied. Manual searches were also conducted manually in journals, abstracts of conferences, and dissertations. There were no restrictions when searching the electronic database regarding the language of publication, study time range, duration of intervention, type of participants, and place of study. Also, the quality of articles was evaluated based on the Jadad index. Findings: 371 articles were obtained in the initial search. 273 articles remained by deleting duplicate articles. 170 articles with study of title and 80 articles with study of abstract were excluded. Finally, 23 articles remained. Of the 23 studies, 12 interventions covered all of the social marketing criteria. Criteria of determining behavioral goal, customer orientation, exchange, segmentation and mix of methods were considered in all studies. Also, competition was observed in 12 interventions. In all studies, some positive changes in healthy eating behavior were reported (p<0.05). Conclusion: Social marketing approach can promote healthy eating behaviors.